Scientific literature on monosialoganglioside in the Science Citation Index-Expanded A bibliometric analysis of articles from 1942 to 2011 by each decade - Xu, Yanli; Li, Miaojing; Liu, Zhijun; Liu, Ruichun; Zhang, Jianzhong (Neural regeneration research, 2012)
BACKGROUND： The monosialoganglioside （GM1） is a popular topic of research but the bibliometric analysis of GM1 over the decades in Science Citation Index-Expanded （SCI-E） remains poorly understood. OBJECTIVE： To identify the global research and to improve the understanding of research trends in the GM1 field from 1942 to 2011. DESIGN： A bibliometric study. DATA RETRIEVAL： We performed a bibliometric analysis based on the SCI-E published by the Institute of Scientific Information. INCLUSIVE CRITERIA： Articles closely related to GM1 were included. Exclusive criteria： （1） Articles related to gangliosidosis, disialo-ganglioside, trisialo-ganglioside or ganglioside GQIb. （2） Document types such as meeting abstracts, reviews, proceedings papers, notes, and letters. MAIN OUTCOME MEASURES： （1） Type of publication output; （2） number of author outputs; （3） distribution of output in subject categories; （4） publication distribution of countries; （5） distribution of output in journals, and （6） distribution of citations in each decade. RESULTS： During 1942 to 2011, there were 10 126 papers on GM1 that were added to the SCI. Articles （8 004） were the most frequently used document type comprising 79.0%, followed by meeting abstracts, reviews and proceedings papers. Research on GM1 could be found in the SCI from 1942, it was developed in the 1970s, greatly increased in the 1980s, and reached a peak in the 1990s, and it was slightly decreased in 2000. The distribution of subject categories showed that GM1 research covered both clinical and basic science research. The USA, Japan, and Germany were the three most productive countries, and the publication numbers in the USA were highest in all decades. The Joumal of Biological Chemistry, Journal of Neurochemistry and Biochemistry were core subject journals in GM1 studies in each decade. CONCLUSION： This study highlights the topics in GM1 research that are being published around the world.